Clinical Characteristics and Metabolic Abnormalities in Pediatric Urolithiasis in South East Iran - Sadeghi, Simin; Fazeli, Faramarz; Zarifi, Elham (Journal of Pediatric Nephrology, 2015)
Introduction: To investigate clinical presentation, metabolic risk factors and urinary tract abnormalities in paediatric urolithiasis. Materials and Methods: Between 2011 and 2012, 100 children (53 boys and 47 girls) were treated for urolithiasis. Clinical presentation, calculus localisation, urinary tract infection status, presence of anatomic abnormalities and urinary metabolic risk factors were retrospectively evaluated. Results: The most common clinical features on admission were restlessness/irritability (62%), flank pain (33%) and gross hematuria (4%). Twenty-one percent of patients were detected incidentally during evaluation for other conditions. Urine random tests revealed metabolic abnormalities, including hypercalciuria (56%) and hypocitraturia (64%) in most cases. Anatomic malformation (32%) and urinary tract infections (UTI)(9%) were other presentations. Conclusions: We concluded that most patients were symptomatic and hypocitraturia was the most common risk factor. Keywords: Urolithiasis; Urinary Tract; Pediatrics, Demographic Factor; Hypercalciuria.